APPLICATION OF LEAN PRINCIPLES IN THE SOUTH AFRICAN CONSTRUCTION INDUSTRY - Maradzano, Isabellah (South African Journal of Industrial Engineering, 2019)
South Africa is a developing country that invests billions of rands annually in the construction industry. This industry consumes resources and, inevitably, waste is generated during the process. Although numerous approaches have been developed to improve quality, efficiency, and effectiveness in this industry, lean principles offer the ability to minimise and/or eliminate non-value adding work, thus increasing value for the client. This paper highlights the lean construction tools currently used worldwide, and the benefits of adopting lean construction. The study surveyed publications on the application of lean principles in the construction industry, and identified tools yet to be implemented in the South African construction industry with specific reference to electrical and mechanical engineering services. The study used a systematic review methodology to identify different lean construction concepts, and developed a lean implementation framework. The framework was then evaluated using a local case focusing on electrical and mechanical engineering services in the construction industry. The improved framework after evaluation consists of eight steps.